Spontaneous Rupture of Choledochal Cyst: A Rare Presentation - P. Juvaina; K.T. Aleena; Arakkal Riyaz; E. Devarajan; P. Ranjit; E.R. Rani Jyothi (Thieme Medical and Scientific Publishers Pvt. Ltd., 2023)
Choledochal cyst (CDC) is a rare surgical cause of cholestatic jaundice in infants. Spontaneous rupture is an unusual presentation of a previously undiagnosed CDC and is also a rare cause of biliary peritonitis in children. Here, we report a case of a 1-year-old boy who was evaluated for progressive abdominal distension. Ultrasonogram showed gross ascites with echogenic particles, dilated common bile duct (CBD), common hepatic duct (CHD), and upstream intra hepatic biliary radicle dilatation (IHBRD). CECT sections of the abdomen showed gross ascites and IHBRD with disproportionate dilatation of CHD and CBD. At laparotomy, a type 1 CDC with rupture of the anterior wall was found. The cyst was excised followed by hepaticojejunostomy. In a sick child with abdominal pain, cholestatic jaundice and biliary ascites, a high index of suspicion during imaging will help in the correct diagnosis and surgery for a potentially fatal ruptured CDC.